Interfacial quality to control tunnelling magnetoresistance - Hirohata, Atsufumi; Elphick, Kelvin; Lloyd, David C.; Mizukami, Shigemi (Frontiers in Physics, 2022)
Theoretically, coherent tunnelling through an MgO barrier can achieve over 1,000% magnetoresistance at room temperature. To date, this has not been demonstrated experimentally. In this article, we have categorised magnetic tunnel junctions into four groups and have investigated possible causes of the reduction in their magnetoresistance by correlating their interfacial atomic structures and spin-polarised electron transport. We have concluded that the spin fluctuation induced by dislocations and disordering at a ferromagnet/barrier interface reduced the corresponding magnetoresistance.